Organic and inorganic geochemical data of sediment cores XC-03 and XC-01-2, Xingu River, Amazon Basin - Dailson José Bertassoli Junior; André Oliveira Sawakuchi; Cristiano Mazur Chiessi; Enno Schefuß; Gelvam André Hartmann; Christoph Häggi; Matthias Zabel; Michael M McGlue; Rudney A Santos; Fabiano Nascimento Pupim (PANGAEA, 2019)
Late Holocene hydroclimate variations have been extensively recognized in Amazonia, but the effects of such changes on riverine discharge within the Amazon lowlands are still poorly understood. We investigated a sediment core covering circa 4,000 to 300 cal yr BP collected in the lower valley of the Xingu River (Xingu Ria) in an area under the influence of the Amazon River. Our results indicate a decrease in precipitation in the Amazon lowlands throughout the studied period and reduced input of coarser and potassium-rich Amazon River sediments to the confluence from about 2,600 to 1,400 cal yr BP. We suggest that lower temperatures in the extratropical Southern Hemisphere weakened the South American Summer Monsoon and led to a decrease in the water discharge of the Amazon River during this period.
Supplement to: Bertassoli Junior, Dailson José; Sawakuchi, André Oliveira; Chiessi, Cristiano Mazur; Schefuß, Enno; Hartmann, Gelvam André; Häggi, Christoph; da Cruz Junior, Francisco William; Zabel, Matthias; McGlue, Michael M; Santos, Rudney A; Pupim, Fabiano Nascimento (2019): Spatiotemporal Variations of Riverine Discharge Within the Amazon Basin During the Late Holocene Coincide With Extratropical Temperature Anomalies. Geophysical Research Letters, 46(15), 9013-9022, https://doi.org/10.1029/2019GL082936